Study on the Austenite Grain Growth Behavior of Fe-Mn-Al-C Low-Density Steel Containing Niobium - Litu Huo; Tao Ma; Weimin Gao; Yungang Li; Haichao Zhang; Jianxin Gao (Metals)
To explore the impact of niobium (Nb) addition on the austenitization behavior of Fe-Mn-Al-C lightweight steels, the effects were examined through Thermo-Calc thermodynamic simulations, optical microscopy, transmission electron microscopy (TEM), and the development of austenite grain growth models. Three distinct Fe-Mn-Al-C steel compositions, each containing different Nb contents (0.38%, and 0.56%), were subjected to various austenitization temperatures and aging conditions, and a kinetic model for austenite grain growth was established. The results demonstrate that for heating temperatures below 950 °C, the austenite grain growth rate of the steels was similar. However, at temperatures above 950 °C, the grain growth rate of the steel without Nb (Steel No. 1) increased significantly compared to the niobium-containing alloys. Austenite grain size increased with higher heating temperatures. At constant heating temperatures, longer holding times resulted in larger grain sizes, though the rate of grain size growth diminished over time. Based on the experimental data and the kinetic theory of austenite grain growth, a grain growth model of No. 2 Steel (which contained 0.38% Nb) was established. The predicted grain size values derived from this model closely matched the experimental measurements, indicating a strong correlation and providing valuable insights for future studies.